2019
DOI: 10.1186/s12957-019-1666-9
|View full text |Cite
|
Sign up to set email alerts
|

Repeat liver resection for pure large cell neuroendocrine carcinoma of the gallbladder: a favorable outcome

Abstract: Background The pure large cell type is a rare variant of primary neuroendocrine carcinoma of the gallbladder. Few reports have mentioned extended survival. Although a multimodal treatment has been described in the treatment of such rare disease, redo liver resection has not yet been mentioned. Case report A 67-year-old lady was found to have poorly differentiated, high grade, pure large cell neuroendocrine tumor of the gallbladder after cholecystectomy for gallstones. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Surgical treatment. Advantages and disadvantages of the various treatment options discussed are listed in Table I: Due to its complexity, gallbladder cancer must be treated surgically by experienced biliary tract physicians and pathologists (42). GB-NEC is characterized by high malignancy, early lymphatic metastasis (the N2 lymph node metastasis rate is significantly higher compared with that of patients with adenocarcinoma in the same period) and a poor prognosis when compared with all other types of gallbladder cancer (20).…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Surgical treatment. Advantages and disadvantages of the various treatment options discussed are listed in Table I: Due to its complexity, gallbladder cancer must be treated surgically by experienced biliary tract physicians and pathologists (42). GB-NEC is characterized by high malignancy, early lymphatic metastasis (the N2 lymph node metastasis rate is significantly higher compared with that of patients with adenocarcinoma in the same period) and a poor prognosis when compared with all other types of gallbladder cancer (20).…”
Section: Treatment Optionsmentioning
confidence: 99%
“… 6 Neuroendocrine tumours of the digestive system have been classified based on mitotic figures and the Ki-67 index, regardless of the origin, size, or anatomic extent of the tumours. 7 As per WHO 2019 updates, GB NEC encompasses small-cell and large-cell types of poorly differentiated NETs with mitotic rate >20mitoses/ 2 mm 2 and/or Ki-67 index >20%. 3 The diagnosis of GB-NEC is based on typical morphological features and immunohistochemistry markers (chromogranin A, synaptophysin, and neuro-specific enolase); pathological results determine tumour grade and staging.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Very few pure LCNEC have been reported in the literature with a median survival of 8 to 10 months, so it becomes very difficult to propose the best management plan. 3 , 7 Still, surgical resection improves overall survival and is the cornerstone in the management of GB-NEC. 5 For neuroendocrine tumours of GB, cholecystectomy could be enough if detected in early stages (in situ and T1 tumours).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abutaka et al had reported a case of pure large cell GBNEC where relentless surgery after a first R0 resection of an NEC of the gallbladder, followed by two hepatic metastasectomy with lymph node dissection had prolonged survival to 26 months [ 18 ].…”
Section: Discussionmentioning
confidence: 99%